The importance of preparing and presenting financial statements in accordance with the SCF and International Accounting Standards - a comparative study between IAS 01 and SCF - Benguetib, ali; hattab, dallel (Journal of Research in Finance and Accounting, 2019)
The study aims to determine the level of preparation and presentation of the financial statements in accordance with the accounting system and the international accounting standards, through a comparative study between the financial accounting system and the accounting standard No. 01 for the preparation and presentation of the financial statements. The results indicated that compliance with this standard of guidance on how to prepare And the presentation of the financial statements would enhance the quality and confidence through its users, and the financial accounting system in Algeria with important clarifications in this area, although characterized by the shortage in some cases. This research is in addition to the existing literature on how the financial statements are prepared and presented by highlighting the practice of this matter in the Algerian financial accounting system.